IMPROVING STUDENTS’ WRITING ABILITY TO WRITE NARRATIVE TEXT THROUGH WRITE PAIR SHARE AT X GRADE OF SMAN 2 KUOK - Putri Asilestari (Universitas Pahlawan Tuanku Tambusai, 2018)
Write Pair Share technique is one of interesting techniques that can be used in teaching writing. Through write pair share, the students have to write any ideas about the topic given, they work in pair to combine ideas, proofreading process, and then shared to their class by submitting the production of narrative story in written form. The purpose of this research is to know the students’ writing ability to write Narrative Text by using write pair share technique. The population of this research is 34 students of X-5 in SMAN 2 Kuok. By using Classroom Action Research, the writer has done two cycle process. After the learning process, the result of first cycle shows that five students who got very good criteria (15%), 19 students who got good criteria (56%), five students who got fair criteria (15%), and five students who got poor criteria (14%). In the second cycle, one student (2.94%) is poor, one student (2.94%) is fair, eight students (23.53%) are good, 18 students (52.94%) are very good and six students (17.65%) are excellent. In conclusion, there are six students get the score under the minimal standard score (≥75) or 82.35% students get higher score than 75. It indicates that write pair share technique is an appropriate technique that can improve students’ writing ability to write narrative text.